Magnesium phosphate regenerated inorganic adhesive for carbon fiber cloth reinforced concrete structure and preparation method thereof

By using a combination of magnesium phosphate regenerated inorganic glue and recycled fine aggregate in carbon fiber cloth-reinforced concrete structures, the problem of performance degradation of traditional binders in high temperature environments is solved, and a reinforced composite material with high strength and good durability is realized. It has the advantage of environmentally friendly carbon emissions.

CN119330682APending Publication Date: 2025-01-21HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411496453.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The bonding performance of existing carbon fiber cloth reinforced concrete structures in high temperature environments is reduced, resulting in failure of reinforcement effect. The high-temperature resistance of traditional epoxy resin glue is insufficient, which limits its application.

Method used

Magnesium phosphate regenerated inorganic glue is used as a binder. By mixing regenerated fine aggregate into the magnesium phosphate inorganic glue, a magnesium phosphate regenerated inorganic glue with good high temperature resistance and durability is prepared, and combined with carbon fiber cloth to form a reinforced composite materials.

Benefits of technology

This method improves the high-temperature resistance and bonding effect of carbon fiber sheet-reinforced concrete structures, has the advantages of rapid hardening, early strength and high strength, while reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330682A_ABST
    Figure CN119330682A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium phosphate regenerated inorganic adhesive for a carbon fiber sheet reinforced concrete structure, which is prepared from 30-48 parts of dead burned magnesium oxide, 20-30 parts of potassium dihydrogen phosphate, 2-6 parts of borax, 6-24 parts of fine aggregate, 3-8 parts of basalt fiber, 5-15 parts of regenerated rubber and 15-20 parts of water, and the preparation method comprises the following steps: step 1, weighing various materials according to the raw material ratio; the preparation method comprises the following steps: step 1, pouring potassium dihydrogen phosphate, fine aggregate, regenerated rubber, basalt fiber, borax, 2 / 3 of dead-burnt magnesium oxide and water into a cement mortar stirrer, and stirring to obtain uniform slurry; step 2, adding the rest 1 / 3 of dead-burnt magnesium oxide and water, and rapidly stirring to obtain magnesium phosphate regenerated inorganic glue; the magnesium phosphate regenerated inorganic adhesive prepared by doping the regenerated fine aggregate into the magnesium phosphate inorganic adhesive has the advantages of high temperature resistance, good durability and excellent bonding effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building structure reinforcement, and in particular to a magnesium phosphate regenerated inorganic adhesive for reinforcing a concrete structure with carbon fiber cloth and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization, the fire safety problem of building structures has become increasingly prominent. At present, the fire safety problem of the carbon fiber cloth reinforcement method is still a technical bottleneck for its promotion and application. There are few reports on the fire-resistant design methods and structural measures of carbon fiber cloth reinforcement with practical significance. Studies have shown that the high temperature resistance of epoxy resin glue is very poor, but epoxy resin does have many advantages, so some scholars have modified epoxy resin glue to prepare high temperature resistant modified epoxy resin glue, but the uneconomical nature of modified epoxy resin glue has also restricted its development.

[0003] Compared with traditional reinforcement methods, the carbon fiber cloth reinforcement method is significantly ahead of the development of reinforcement theory; however, since epoxy organic adhesives will soften after exceeding the glass transition temperature (65℃~82℃), their performance will be greatly reduced. Therefore, the long-term use temperature of the carbon fiber cloth reinforced concrete structure should not exceed 60℃; when the temperature of the bonding layer reaches the glass transition temperature, the positive tensile bond strength between the carbon fiber cloth and the concrete drops to 20%~28% of that at room temperature, and the in-plane shear strength also decays significantly; when the temperature reaches 150℃, the in-plane shear strength decays to zero, and the basis for transmitting the shear force between the carbon fiber cloth layers and working with the concrete is lost;

[0004] During a fire, the ambient temperature inside a building can reach over 1000°C. If there are no reliable fire protection measures on the surface of the carbon fiber cloth reinforced concrete member, the bonding performance of the low softening point organic glue will be significantly reduced, resulting in the peeling of the carbon fiber cloth and the matrix concrete, and the reinforcement effect will fail. Therefore, the present invention proposes a magnesium phosphate regenerated inorganic glue for carbon fiber cloth reinforced concrete structure and a preparation method to solve the problems existing in the prior art. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to propose a magnesium phosphate regenerated inorganic glue for carbon fiber cloth reinforced concrete structure and a preparation method. The preparation method of magnesium phosphate regenerated inorganic glue for carbon fiber cloth reinforced concrete structure is that the magnesium phosphate regenerated inorganic glue prepared by adding recycled fine aggregate into the magnesium phosphate inorganic glue has the advantages of high temperature resistance, good durability and excellent bonding effect. When combined with carbon fiber to form a reinforced composite material, it has the advantages of fast hardening, early strength and high strength.

[0006] To achieve the purpose of the present invention, the present invention is implemented through the following technical scheme: a magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, comprising dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine aggregate, basalt fiber, recycled rubber and water in the weight proportions of 30 to 48 parts, 20 to 30 parts, 2 to 6 parts, 6 to 24 parts, 3 to 8 parts, 5 to 15 parts and 15 to 20 parts.

[0007] A further improvement is that the dead-burned magnesium oxide is a mixture of one or more of MgO, Al2O3, Fe2O3, CaO, SO2, TiO2, Na2O, and SO3; and the fine aggregate is made by mixing recycled fine aggregate with a particle size of 2mm to 5mm and ceramsite in a mass ratio of 2.8 to 3.7:2.2 to 3.1.

[0008] A further improvement is that the recycled fine aggregate is one of glass powder, recycled stone powder, recycled brick powder and recycled cement; wherein the recycled stone powder is a powder with a fineness of 800 mesh obtained by grinding and sieving recycled stone powder.

[0009] A method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth comprises the following steps:

[0010] Step 1: Weigh various materials according to the raw material ratio, then pour potassium dihydrogen phosphate, fine aggregate, recycled rubber, basalt fiber, borax and 2 / 3 of dead-burned magnesium oxide into a cement mortar mixer and dry mix for 1 minute, then slowly add 2 / 3 of the total water and continue stirring to obtain a uniform slurry;

[0011] Step 2: Then add the remaining 1 / 3 of dead-burned magnesium oxide and water and stir rapidly for 3 to 4 minutes before discharging to obtain magnesium phosphate regenerated inorganic glue.

[0012] The further improvement is that: the preparation of potassium dihydrogen phosphate in the step 1 is specifically as follows: 6 mol / L phosphoric acid is first added to a round-bottom flask, then 250 ml of 6 mol / L potassium hydroxide is poured into the flask using a glass rod for drainage, and heated under reflux at a temperature of 400° C. to generate a precipitate, and then the precipitate is filtered to concentrate the filtrate to a relative density of 1.32, and the precipitate is cooled and filtered to remove the crystals, and the crystals are washed with ionized water, and then dried to obtain potassium dihydrogen phosphate.

[0013] A further improvement is that the preparation of basalt fiber in step 1 is specifically to put 10g of basalt stone into a calcining furnace, place it at a temperature of 1450°C to 1500°C for 10 minutes, and after the basalt stone is melted, it is drawn at high speed using a platinum-rhodium alloy bushing to obtain continuous basalt fiber.

[0014] A further improvement is that the preparation of dead-burned magnesium oxide in step 2 is specifically to first place the dolomite in a kiln for high-temperature calcination at 1700°C, then grind the calcined material into brown-yellow granular materials of different particle sizes, and then sieve to retain the powder with a particle size of ≤15mm to obtain dead-burned magnesium oxide.

[0015] A further improvement is that the magnesite used is a mineral with MgCO3 as the main component, with a mud content of ≤0.83%, a mud block content of ≤0.4%, a solidity index of ≤10.0%, a light material content of ≤1.0%, and a sulfide and sulfate content of ≤1.0%.

[0016] The beneficial effects of the present invention are as follows: the magnesium phosphate regenerated inorganic glue prepared by adding recycled fine aggregate into the magnesium phosphate inorganic glue has the advantages of high temperature resistance, good durability and excellent bonding effect. It is matched with carbon fiber to form a reinforced composite material with the advantages of fast hardening, early strength and high strength. At the same time, compared with traditional inorganic glues, the magnesium phosphate regenerated inorganic glue of the present invention can effectively reduce carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart of the preparation method.

[0018] Figure 2 This is an X-ray diffraction analysis diagram of the magnesium phosphate regenerated inorganic glue of the present invention.

[0019] Figure 3 These are SEM images of different fiber-reinforced magnesium phosphate regenerated inorganic adhesives of the present invention.

[0020] Figure 4 This is a SEM image of the borax-reinforced magnesium phosphate regenerated inorganic glue of the present invention.

[0021] Figure 5 These are SEM images of magnesium phosphate regenerated inorganic adhesive used for bonding carbon fiber cloth to reinforce concrete structure at different temperatures of the present invention. DETAILED DESCRIPTION

[0022] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0023] according to Figure 1-Figure 5As shown, this embodiment provides a magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, including heavy-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine aggregate, basalt fiber, recycled rubber and water in the weight parts of 30-48 parts, 20-30 parts, 2-6 parts, 6-24 parts, 3-8 parts, 5-15 parts and 15-20 parts; the fine aggregate is made by mixing recycled fine aggregate with a particle size of 2mm-5mm and ceramsite in a mass ratio of 2.8-3.7:2.2-3.1.

[0024] Example 1

[0025] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0026] Weigh by weight. Amount of cementitious material: 48% magnesium oxide, 25% potassium dihydrogen phosphate, 3% basalt fiber. Amount of admixture: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1 to 2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. Obtain magnesium phosphate regenerated inorganic cementitious material for testing compressive and flexural strength.

[0027] The magnesium phosphate regenerated inorganic gelling material prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 170~180mm, initial setting time 15~20min, final setting time 60~65min, initial compressive strength can reach 77.2~77.9MPa, and initial flexural strength is 8.0~8.3MPa.

[0028] Example 2

[0029] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0030] The amount of cementitious materials used: 46% magnesium oxide, 25% potassium dihydrogen phosphate, and 5% basalt fiber. The amount of admixtures used: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, borax, and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1 to 2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regeneration inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0031] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 86.7~87.2MPa, and initial flexural strength is 13.1~13.2MPa.

[0032] Example 3

[0033] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0034] The amount of cementitious materials: 43% magnesium oxide, 25% potassium dihydrogen phosphate, and 8% basalt fiber. The amount of admixtures: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1 to 2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regeneration inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0035] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 80.1~80.2MPa, and initial flexural strength is 11.8~12.2MPa.

[0036] Example 4

[0037] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0038] Put the regenerated stone powder into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 40% magnesium oxide, 8% regenerated stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated stone powder, borax and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material for testing the compressive and flexural strength is obtained.

[0039] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 165~170mm, initial setting time 15~20min, final setting time 70~75min, initial compressive strength can reach 80.2~87.1MPa, and initial flexural strength is 8.4~8.9MPa.

[0040] Example 5

[0041] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0042] Put the regenerated stone powder into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 36% magnesium oxide, 12% regenerated stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated stone powder, borax and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0043] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 165~170mm, initial setting time 15~20min, final setting time 70~80min, initial compressive strength can reach 77.6~81.4MPa, and initial flexural strength is 7.5~8.3MPa.

[0044] Example 6

[0045] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0046] Put the regenerated stone powder into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 33% magnesium oxide, 15% regenerated stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated stone powder, borax and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0047] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 61.3~64.2MPa, and initial flexural strength is 4.4~4.6MPa.

[0048] Example 7

[0049] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0050] Put the regenerated stone powder into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 26% magnesium oxide, 24% regenerated stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated stone powder, borax and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0051] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 220~230mm (fluidity is too high), initial setting time 20~25min, final setting time 115~120min (final setting time is too long), initial compressive strength can reach 57.6~63.0MPa (slightly lower strength), and initial flexural strength is 4.1~4.2MPa (slightly lower strength).

[0052] Example 8

[0053] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0054] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 46% magnesium oxide, 2% regenerated rubber, 25% potassium dihydrogen phosphate, 3% basalt fiber. The amount of admixtures: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0055] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 69.4~72.4MPa, and initial flexural strength is 3.4~4.2MPa.

[0056] Example 9

[0057] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0058] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 45% magnesium oxide, 3% regenerated rubber, 25% potassium dihydrogen phosphate, 3% basalt fiber. The amount of admixtures: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0059] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 57.0~57.6MPa, and initial flexural strength is 4.0~4.8MPa.

[0060] Example 10

[0061] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0062] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 43% magnesium oxide, 5% regenerated rubber, 25% potassium dihydrogen phosphate, 3% basalt fiber. The amount of admixtures: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0063] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 39.4~40.9MPa, and initial flexural strength is 4.0~5.1MPa.

[0064] Embodiment 11

[0065] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0066] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 40% magnesium oxide, 8% regenerated rubber, 25% potassium dihydrogen phosphate, 3% basalt fiber. The amount of admixtures: 5% borax, 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0067] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 71.5~82.6MPa, and initial flexural strength is 8.1~8.7MPa.

[0068] Example 12

[0069] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0070] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 38% magnesium oxide, 10% regenerated rubber, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0071] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 70.5~77.6MPa, and initial flexural strength is 7.8~8.1MPa.

[0072] Embodiment 13

[0073] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0074] Put the regenerated rubber into a grinder and grind it to 0.5-1um for use; the amount of cementitious materials: 33% magnesium oxide, 15% regenerated rubber, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, regenerated rubber, borax and fiber into a stirring pot and mix and stir for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue stirring for 1-2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate regenerated inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0075] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity is too small), initial setting time 15~20min, final setting time 100~110min (final setting time is too long), initial compressive strength can reach 61.9~66.6MPa, and initial flexural strength is 3.8~4.3MPa.

[0076] Embodiment 14

[0077] This embodiment provides a method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, which is as follows:

[0078] The amount of cementitious materials: 33% magnesium oxide, 15% recycled rubber, 25% potassium dihydrogen phosphate, and 3% basalt fiber. The amount of admixtures: 5% borax and 19% water. At room temperature, first pour 2 / 3 of magnesium oxide and water and all potassium dihydrogen phosphate, borax, and fiber into a stirring pot and mix for 1 minute, then pour the remaining magnesium oxide and water into the stirring pot and continue to stir for 1 to 2 minutes, and finally inject the slurry into a steel mold and let it stand for 28 days. The magnesium phosphate recycled inorganic cementitious material used to test the compressive and flexural strength is obtained.

[0079] The magnesium phosphate regenerated inorganic glue prepared in the example for testing the compressive and flexural strength was injected into a steel mold of 100mm×100mm×100mm, and its performance parameters were measured as follows: fluidity 140~150mm (fluidity too small), initial setting time 15~20min, final setting time 100~110min (final setting time too long), initial compressive strength can reach 84.8~85.2MPa, and initial flexural strength is 12.0~12.6MPa.

[0080] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A magnesium phosphate regenerated inorganic adhesive for reinforcing concrete structure with carbon fiber cloth, characterized in that: The invention comprises dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, fine aggregate, basalt fiber, regenerated rubber and water in proportions of 30-48 parts, 20-30 parts, 2-6 parts, 6-24 parts, 3-8 parts, 5-15 parts and 15-20 parts by weight.

2. The magnesium phosphate regenerated inorganic adhesive for reinforcing concrete structure with carbon fiber cloth according to claim 1, characterized in that: The dead-burned magnesium oxide is a mixture of one or more of MgO, Al2O3, Fe2O3, CaO, SO2, TiO2, Na2O, and SO3; the fine aggregate is prepared by mixing recycled fine aggregate with a particle size of 2mm to 5mm and ceramsite in a mass ratio of 2.8 to 3.7:2.2 to 3.

1.

3. The magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth according to claim 2, characterized in that: The recycled fine aggregate is one of glass powder, recycled stone powder, recycled brick powder and recycled cement; wherein the recycled stone powder is a powder with a fineness of 800 mesh obtained by grinding and sieving recycled stone powder.

4. A method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth, characterized in that: The following steps are involved: Step 1: Weigh various materials according to the raw material ratio, then pour potassium dihydrogen phosphate, fine aggregate, recycled rubber, basalt fiber, borax and 2 / 3 of dead-burned magnesium oxide into a cement mortar mixer and dry mix for 1 minute, then slowly add 2 / 3 of the total water and continue stirring to obtain a uniform slurry; Step 2: Then add the remaining 1 / 3 of dead-burned magnesium oxide and water and stir rapidly for 3 to 4 minutes before discharging to obtain magnesium phosphate regenerated inorganic glue.

5. The method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth according to claim 4, characterized in that: The preparation of potassium dihydrogen phosphate in the step 1 is specifically as follows: first, 6 mol / L phosphoric acid is added into a round-bottom flask, then 250 ml of 6 mol / L potassium hydroxide is poured into the flask using a glass rod, and then heated under reflux at a temperature of 400° C. to generate a precipitate, and then the precipitate is filtered to concentrate the filtrate to a relative density of 1.32, and then cooled and filtered to remove crystals, and the crystals are washed with ionized water, and then dried to obtain potassium dihydrogen phosphate.

6. The method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth according to claim 4, characterized in that: The preparation of basalt fiber in step 1 is specifically as follows: 10 g of basalt stone is placed in a calcining furnace, placed at a temperature of 1450° C. to 1500° C. for 10 minutes, and after the basalt stone is melted, it is drawn at high speed using a platinum-rhodium alloy bushing to obtain continuous basalt fiber.

7. The method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth according to claim 4, characterized in that: The preparation of dead-burned magnesium oxide in step 2 is specifically as follows: firstly, magnesite is placed in a kiln for high-temperature calcination at 1700° C., then the calcined material is ground into brown-yellow granular materials of different particle sizes, and then the powder with a particle size of ≤15 mm is sieved to obtain dead-burned magnesium oxide.

8. The method for preparing magnesium phosphate regenerated inorganic glue for reinforcing concrete structure with carbon fiber cloth according to claim 7, characterized in that: The magnesite used is a mineral with MgCO3 as the main component, with mud content ≤0.83%, mud block content ≤0.4%, solidity index ≤10.0%, light material content ≤1.0%, sulfide and sulfate content ≤1.0%.

Citation Information

Cited By

  • Magnesium phosphate inorganic adhesive as well as preparation method and application thereof

    CN120505044A